2007
DOI: 10.1111/j.1530-0277.2006.00320.x
|View full text |Cite
|
Sign up to set email alerts
|

Stress‐Induced and Alcohol Cue‐Induced Craving in Recently Abstinent Alcohol‐Dependent Individuals

Abstract: Background: Research has shown that exposure to stress/negative affect and to alcohol cues can each increase alcohol craving and relapse susceptibility in alcohol-dependent individuals. However, whether the emotional and physiological states associated with stress-induced and alcohol cueinduced craving are comparable has not been well studied. Therefore, this study examined the craving, emotional, and physiological responses to stress and to alcohol cues in treatment-engaged, 4-week abstinent, alcohol-dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
264
0
5

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 289 publications
(289 citation statements)
references
References 87 publications
(86 reference statements)
20
264
0
5
Order By: Relevance
“…Coding trials to capture these temporal variations could reveal additional effects of salient stimuli. Whether similar effects are seen with other stressors, such as guided imagery (Fox et al, 2007), is another important question, given that uncontrollable noise may not fully characterize the stressful conditions that precipitate relapse outside the laboratory.…”
Section: Stress and Alcohol Cues On Go-stop Responding M Zack Et Almentioning
confidence: 99%
“…Coding trials to capture these temporal variations could reveal additional effects of salient stimuli. Whether similar effects are seen with other stressors, such as guided imagery (Fox et al, 2007), is another important question, given that uncontrollable noise may not fully characterize the stressful conditions that precipitate relapse outside the laboratory.…”
Section: Stress and Alcohol Cues On Go-stop Responding M Zack Et Almentioning
confidence: 99%
“…Nevertheless, there are many reports of spontaneous relapse of drug-taking, even though drug cue reactivity had previously been significantly reduced or eliminated by drug cue extinction procedures (Wikler, 1973;Monti et al, 2001;Junghanns et al, 2005;Loeber et al., 2006), and Hammersley (1992) has attributed relapse to drug-taking following cue extinction therapy to spontaneous recovery. A role for spontaneous recovery of sign-tracking in relapse to drugtaking is suggested by reports that alcohol drinking glassware provides cues eliciting alcoholrelated physiological responses (Carter and Tiffany, 1999) and subjective cravings for alcohol (Cooney et al, 1983;Fox, 2007), and the persistence of these cue-elicited responses contribute to relapse (Marlatt, 1990;Rohsenow et al, 1994;Sinha and Li, 2007).…”
Section: Relapse-like Effectsmentioning
confidence: 99%
“…Moreover, these changes have been documented during protracted cocaine abstinence (Mantsch et al 2003;Zhou et al 2003) alongside a range of symptoms comprising dysphoria, anxiety, and increased sensitivity to stress and craving (Kampman et al 2001;Mulvaney et al 1999). Recent laboratory studies have also shown increased sensitivity to stress-induced craving, HPA axis function, and negative emotion in recently abstinent cocaine (Fox et al 2007a;Sinha et al 2003) and alcohol (Fox et al 2007b;Sinha et al 2005) dependent individuals. Notably, these factors have been shown to be sex-specific (Fox et al 2006a;Kirschbaum et al 1999) and integral to relapse (Adinoff et al 2005;Sinha et al 2006).…”
Section: Introductionmentioning
confidence: 99%